The Anti-Inflammatory Potential of a Combination of Centella asiatica Leaf and Caesalpinia sappan Wood Ethanol Extracts: - - -, IRMA SANTI; Sukmawati, Sukmawati; Wijayanti, Etri (Ad-Dawaa' Journal of Pharmaceutical Sciences, 2025)
Introduction: Inflammation is the body's response to infection and tissue damage by sending the body's cells and defense molecules from the bloodstream to the location needed to eliminate the cause of the damage. Centella asiatica L. and Caesalpinia sappan L. contain tannin, phenolic, and flavonoid compounds that are effective as anti-inflammatories. Objective: This study aimed to test the anti-inflammatory potency and effective dose of Centella asiatica leaves and Caesalpinia sappan wood, in male rats (Rattus norvegicus). Methods: 20 wistar rats were divided into five treatment groups: a negative control group (CMC Na 1%), a positive control group (Diclofenac Sodium), and three combination groups of a combination Centella asiatica leaves and Caesalpinia sappan wood ethanol extracts (EEPS) with dose variations of 250:375 mg/kgBW, 200:400 mg/kgBW, and 150:425 mg/kgBW. Intraplantar edema induction with lambda carrageenan. parameter measured of edema volume with a plethysmometer and edema thickness with a caliper. Results: The combination of ethanol extract showed anti-inflammatory effects at all doses, which showed a decrease in the volume and thickness of edema at 180 to 360 minutes. At the dose 150:425 mg/kgBW shows total inflammatory response during the observation period is seen from the area under curve (AUC) value where AUC value of edema volume of 21.50 and an AUC value of edema thickness of 46.70. In addition, at this dose, percentage of anti-inflammatory activity (%DAI) where the value of %DAI at edema volume is 34% and %DAI at edema thickness is 22%. Conclusion: The combination of ethanol extract has an anti-inflammatory effect, as well as an effective dose to reduce the volume and thickness of edema in male rats (Rattus norvegicus), namely a dose of 150:425 mg/kgBW.